(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Women in the workforce often face unique nutritional challenges due to demanding schedules, work-related stress, and limited access to healthy food options during working hours. This study aims to evaluate the effectiveness of workplace nutrition interventions on the clinical health outcomes of female employees. Using a mixed-methods approach, we assessed dietary behaviors, biometric markers (BMI, blood glucose, lipid profile), and self-reported health indicators before and after the implementation of tailored nutritional programs in three corporate settings. Interventions included structured meal planning, nutrition education sessions, provision of healthy snacks, and digital dietary tracking tools. After 12 weeks, participants showed significant improvements in dietary quality, reductions in BMI and fasting glucose levels, and reported enhanced energy levels and mental well-being. These findings suggest that targeted workplace nutrition interventions can be a valuable strategy in promoting better health among working women. Further longitudinal studies are recommended to assess the sustainability and long-term clinical impacts of such programs.